The Effect of Project-Based Learning (PjBL) Based Audio Visual Media to Improve the Learning Outcomes of Grade VI Students of SD N 056613 Gemi Beach - Seni Sehati Br. Surbakti (Education Achievement: Journal of Science and Research, 2024)
The research using the Influence of Audio Visual Media based on Project Based Learning (PjBl) is to improve students' critical thinking skills on the ecosystem subtheme on the learning outcomes of the science material "The Influence of Human Activities on Ecosystem Balance" through audio visual media in class VI SDN 056613 Pantai Gemi. This research data was obtained from the results of the classroom action research method (Classroom Action Research) carried out by the teacher in class VI with a total of 40 students, where the research was carried out through the stages of recording, carrying out actions, observing and reflecting. The results obtained from this research are an increase in science learning outcomes in class VI SDN 056613 Pantai Gemi. In cycle I, student learning outcomes were 65%. In cycle II 75% of student learning outcomes had achieved what was desired. Data obtained from the results of observations of teaching teachers which have been carried out by observers have increased in cycles I and II. The percentage of implementation from 75% in cycle I increased to 95% in cycle II. In cycle I, the implementation indicators reached 75% of the 11 indicators implemented. . The implication of the results of this research is that using audio visual media based on Project Learning (PjBl) can be used as a means to increase learning motivation and science learning outcomes in the material Influence of Human Activities on Ecosystem Balance for class VI elementary school 056613 Pantai Gemi.